Predicting Consumer Purchasing Decision from Product Quality and Promotion through Brand Image - Asep Saputra (Journal of Business and Management Review, 2022)
This study aims to examine the effect of product quality and promotion on purchase decision with brand image as mediating variable. The research population were the consumers who have purchased and used a Xiaomi smartphone in Cirebon City. 100 respondents were taken as the research sample by non-probability using purposive sampling. The technique used for data analysis was path analysis using SPSS 26.0 for windows. The result showed that product quality has a positive and significant effect on brand image, product quality has a positive and significant effect on purchase decision, promotion has a positive and significant effect on brand image, promotion has a positive and significant effect on purchase decision, brand image has a positive and significant effect on purchase decision, brand image mediates the effect of product quality on purchase decision positively and significantly, brand image mediates the effect of promotion on purchase decision positively and significantly.